Cost-effectiveness analysis of tislelizumab plus chemotherapy versus placebo plus chemotherapy as first-line treatment for advanced gastric or gastroesophageal junction adenocarcinoma: perspectives from the United States and China - Lang, Wenwang; Ai, Qi; Zhang, Wenwen; Jiang, Qinling; He, Yulong; Ouyang, Ming (Frontiers in Pharmacology, 2024)
Purpose: The efficacy of tislelizumab plus chemotherapy in improving progression-free survival (PFS) and overall survival (OS) in unresectable gastric or gastroesophageal junction cancer (GC/GEJC) has recently been emphasized. This study compared the cost-effectiveness of tislelizumab plus chemotherapy versus placebo plus chemotherapy for the United States (US) and Chinese populations. Methods: Using data from the RATIONALE-305 phase 3 trial, a Markov model was developed to analyze quality-adjusted life years (QALYs), incremental cost-effectiveness ratios (ICERs), incremental net health benefits (INHBs), and incremental net monetary benefits (INMBs). The health state utilities and direct medical costs were obtained from the relevant literature and local cost databases. The model uncertainty was evaluated using sensitivity analyses.